Outcome and complications of Ventralex mesh repair in umbilical hernia - Krisna Rani Majumder (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
In recent time, various techniques have been applied for the hernia repair surgery. Considering the possibility of the recurrence rates up to 40%, umbilical and umbilical port hernias have been repaired without mesh for a long time. The repair of these hernias by the Ventralex hernia patch may decrease recurrent hernia rates. The aim of this study was to evaluate the outcome and complications of mesh repair in umbilical hernia by the Ventralex hernia patch. A total of 36 patients were studied retrospectively who underwent mesh repair surgery by the Ventralex hernia patch between April 2017 and October 2019 at Anower Khan Modern Medical College & Hospital, Care Medical College & Hospital and LABAID Specialized Hospital. They have also been evaluated for instant post-operative complications, recurrence rate & pain. Short-term clinical outcomes were assessed during post-operative follow up at first and sixth week. One year long-term outcomes were assessed over telephone. In this study, there were 28 female and 8 male patients with the range of age from 24-68 years (Mean 41.5 ±8.36) having 27 umbilical hernias and 9 umbilical port hernias. No major short-term complications were found but early minor complications were found in 5 patients (13.89%). No pain or mild pain was reported in 31 patients after one week’s post-operative follow up. 34 patients reported being very satisfied with their repairs. In this study we found that the Ventralex hernia patch is an effective and easier technique for mesh repair in umbilical and umbilical port hernias. This technique can also save the operative time with less post-operative complications and better outcomes.